Potensi dan Pemanenan Buah Rotan Jernang - Juang Rata Matangaran; Lana Puspitasari (Jurnal Silvikultur Tropika, 2012)
Potential and Harvesting of Jernang Rattan FruitOne kinds of Non Timber Forest Products (NTFPs) which high economic value is a product derived from rattan fruit called “jernang” or dragon blood’s. Jernang is used for colloring in batik industry and porcelain industry, as a mixture of cure such as wounds medicine.  The research was conducted to analyse  the potential of jernang  rattan fruit and to describe the technique of harvesting jernang rattan fruit of the community. The reseach was conducted at natural forest and community forest at  Sarolangun district at Jambi Province.Potential of jernang at natural forest is 96.51 tons per year and form the community forest is 130.16 ton per year, therefore the total potential of jernang from Sarolangun district is about 226.66 tons per year.The mature fruit which suitable to be harvested is the rippen enough. The colour of ripe jernang fruit which suitable to be harvested is the brownish red color. The fruit takes time about 11−13 months to be ripe fruit. Farmers harvest the fruit by using a hook tool and a pole, then if the rattan is too high the farmer climbs its host tree.